The Effectiveness of Dance Studio Management in Public Senior High Schools and Islamic Senior High Schools in Pekanbaru City - Desi Fitriani; Sumarno; Arza Aibonotika; Daeng Ayub Natuna (Journal of Creative Power and Ambition (JCPA), 2026)
This study examines the effectiveness of dance studio management in Public Senior High Schools (SMAN) and Islamic Senior High Schools (MAN) in Pekanbaru City. Using a qualitative descriptive approach and the CIPPO evaluation model, data were collected through observation, interviews, and documentation in five schools: SMAN 10, SMAN 6, SMAN 4, MAN 2, and MAN 3 Pekanbaru. Informants included principals, advisors, instructors, and student members. Data were analyzed through reduction, display, conclusion drawing, and triangulation. The findings show that dance studio management is generally moderately effective. Stronger effectiveness appears in schools with clear goals, stable trainers, written planning, regular practice, adequate facilities, and systematic evaluation. Weaknesses are found in event-based programs with limited funding, inadequate facilities, unstable schedules, and poor documentation. The study concludes that managerial commitment, policy support, resource stability, and schedule coordination are key to strengthening dance studios as spaces for talent development, cultural preservation, achievement, and character building.